Towards sustainable aviation - Upham, Paul, 1966- (Earthscan Publications, 2003)
Aviation is integral to the global economy but it is also one of the main obstacles to environmentally sustainable development. It is one of the world's fastest growing - and most polluting - industries. What can be done to retain the economic and other benefits it brings without the associated pollution noise congestion and loss of countryside? In this volume industry policy and research experts examine how to address the problems and what it would take to achieve genuinely sustainable aviation - looking at technological policy and demand-management options. Without far-reaching changes the p.